1986
DOI: 10.1107/s0108768186098518
|View full text |Cite
|
Sign up to set email alerts
|

How to avoid unnecessarily low symmetry in crystal structure determinations

Abstract: A check of recent volumes of Acta Crystallographica and Crystal Structure Communications shows that about 3% of all recently published crystal structures were described with too low symmetry. Three categories of error are recognized: (1) both Laue class and crystal system are wrong; (2) only the Laue class is wrong; (3) Laue class and crystal system are correct, but an inversion center is missing. Category (1) cases can be most easily diagnosed by calculating the reduced cell and its Niggli matrix. Category (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 28 publications
0
45
0
1
Order By: Relevance
“…metry. Several crystal structure determinations had been performed with space groups of incorrectly low symmetry (Baur & Tillmanns, 1986) and there are instances of wrong space-group assignments which lead to more than one molecule in the asymmetric unit of the reported low-symmetry space group. For example, N-methylacetamide hemihydrochloride [originally described as C2, Z = 8; Jaber, Guilhem & Loiseleur (1983)] is correctly described as orthorhombic, Fdd2, with one molecule in the asymmetric…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…metry. Several crystal structure determinations had been performed with space groups of incorrectly low symmetry (Baur & Tillmanns, 1986) and there are instances of wrong space-group assignments which lead to more than one molecule in the asymmetric unit of the reported low-symmetry space group. For example, N-methylacetamide hemihydrochloride [originally described as C2, Z = 8; Jaber, Guilhem & Loiseleur (1983)] is correctly described as orthorhombic, Fdd2, with one molecule in the asymmetric…”
Section: Discussionmentioning
confidence: 99%
“…Space-group frequencies for protein crystal structures from the Protein Data Bank, Brookhaven, have been calculated and are compared with those of chiral small molecules. (Baur & Tillmanns, 1986;Marsh, 1986 We report here the frequency for each of the 230 Ima2 46 1 space groups for all compounds which have more than one formula unit in the asymmetric unit. The analysis was made on the Cambridge Structural Database (CSD: release of 1987; see e.g.…”
mentioning
confidence: 99%
“…However, with a distance least-squares (DLS) structure of kaolinite as a starting model (Bish and Von Dreele, 1989), the resulting refined structure was crystal-chemically reasonable and the weighted profile residuals were significantly lower (18.0% for the P1 starting model vs. t2.3% with the DLS starting model). Baur and Tillmanns (1986) suggested that these aspects are characteristic of refinements conducted using unnecessarily low symmetry. Thus, the refinement and partial structure solution of kaolinite were conducted using space group C1; there is no substantive evidence for lower space group symmetry.…”
Section: The Space Group Of Kaolinitementioning
confidence: 99%
“…Baur & Tillmanns, 1986;Marsh, 1986) we believe that the structure is better described, at 153 K also, in the higher-symmetry space group R3 with disordered (instead of ordered) NMeg cations, at least as long as H atoms are not being considered and special attention is paid to the weak reflections. Suzuki, Shin, Hayamizu & Yamamoto, 1985;Derouane & Nagy, 1987).…”
Section: Non-centrosymmetric Arrangement? Considering Thementioning
confidence: 99%